Properties of multiple G.A mismatches in stable oligonucleotide duplexes. - Lane, A; Ebel, S; Brown, T (1994)
The solution structure of the deoxydecanucleotide [sequence: see text] has been determined by NMR methods. This duplex, which contains six G.A mismatches and four Watson-Crick base pairs, is thermodynamically more stable than a decamer where T.A base pairs are substituted for the G.A mismatches, and is less stable than the duplex that contains G.C base pairs. Circular-dichroism spectroscopy indicates an overall B-like conformation for the decamer, but stronger than usual base stacking. 1H-NMR spectroscopy revealed that the N1H groups of the mismatched guanine residues are not hydrogen bonded, and 31P-NMR showed the presence of BII phosphate conformations for the GpA steps. Detailed analysis of the NMR data showed that all nucleotides have anti glycosidic torsion angles and S type sugar puckers. The G.A mismatches pair in the amino form as originally proposed by Li et al. [Li, Y., Zon, G. and Wilson, W. D. (1991) Proc. Natl Acad. Sci. USA 88, 26-30], which results in extensive base-base stacking between the tandem G.A base pairs and their nearest neighbours. The terminal G.A base pairs are less stable than the central base pairs and show evidence of an equilibrium between two conformations, one involving BII phosphate.